NAZARBAYEV UNIVERSITY HOUSING MANAGEMENT SYSTEM - Ishanov, Aktilek; Zakaryanov, Miras; Agadil, Nurbergen; Tashenova, Ralina; Sansyzbay, Temirlan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This project presents the design and development of the NU Housing Management System — a full-stack web application aimed at modernizing and streamlining dormitory operations at Nazarbayev University. The existing manual and spreadsheet-based workflows led to inefficiencies in room assignments, maintenance tracking, and contract management. Our solution integrates core housing functionalities into a centralized platform built using React.js for the frontend, Spring Boot for the backend, and PostgreSQL for data storage. Key features include real-time room allocation, role-based user access, maintenance request handling, and an administrative dashboard. The system was developed iteratively using Agile methodology and validated through multiple feedback sessions with the university’s Housing Management Department. The result is a scalable, modular system designed to enhance both administrative efficiency and student experience.
Keywords: Housing Management System; Web Application; Dormitory Management; Maintenance Tracking; Room Assignment; type of access: open access